L'européisme militant de Grégoire Polet : l'utopie politique de Tous - Almeida, José Domingues de (2021)
This article is concerned with some issues, proposals and impasses that, in recent years, the idea and practice of "European literature" has led us to. Although this endeavor does not overlap, nor does it have to, with that of the European Union, neither is it completely aloof from the challenges of building and consolidating a consciousness of plural unity. These proposals at once confirm the ineffectiveness, or even the logical and practical impossibility of thinking about literary Europe through a simple summation of the literatures of European nations and their histories, and, on the other hand, they show us how literary Europe works as a sample of sensible intelligence of the coordination of differences or individualities.